Hypothalamic reactivity and connectivity following intravenous glucose administration - Simon, Joe J.; Lang, Pia M.; Rommerskirchen, Lena; Bendszus, Martin; Friederich, Hans-Christoph (International journal of molecular sciences, 2023)
Dysfunctional glucose sensing in homeostatic brain regions such as the hypothalamus is interlinked with the pathogenesis of obesity and type 2 diabetes mellitus. However, the physiology and pathophysiology of glucose sensing and neuronal homeostatic regulation remain insufficiently understood. To provide a better understanding of glucose signaling to the brain, we assessed the responsivity of the hypothalamus (i.e., the core region of homeostatic control) and its interaction with mesocorticolimbic brain regions in 31 normal-weight, healthy participants. We employed a single-blind, randomized, crossover design of the intravenous infusion of glucose and saline during fMRI. This approach allows to investigate glucose signaling independent of digestive processes. Hypothalamic reactivity and connectivity were assessed using a pseudo-pharmacological design and a glycemia-dependent functional connectivity analysis, respectively. In line with previous studies, we observed a hypothalamic response to glucose infusion which was negatively related to fasting insulin levels. The observed effect size was smaller than in previous studies employing oral or intragastric administration of glucose, demonstrating the important role of the digestive process in homeostatic signaling. Finally, we were able to observe hypothalamic connectivity with reward-related brain regions. Given the small amount of glucose employed, this points toward a high responsiveness of these regions to even a small energy stimulus in healthy individuals. Our study highlights the intricate relationship between homeostatic and reward-related systems and their pronounced sensitivity to subtle changes in glycemia.
Gesehen am 07.06.2023